Design of a superb Eu2+–Mn2+ co‐doped narrow‐band green phosphor via nearly 100% energy transfer efficiency. Issue 2 (30th October 2022) - Lu, Guangtao; Wang, Yichao; Piao, Siqi; Zhang, Jinsu; Zhang, Xizhen; Zhou, Xufeng; Cao, Yongze; Li, Xiangping; Chen, Baojiu
Abstract: The excellent narrow‐band emitters, especially the green ones, are regarded as a pivotal research direction for light‐emitting diodes (LED) backlights in liquid‐crystal displays (LCDs). A nearly single‐peak green emission centered at 513 nm with a full width at half maximum of 28 nm is reached in KAl11 O17 :0.1Eu 2+, 0.15Mn 2+ phosphor via nearly 100% energy transfer (ET) efficiency, and the extended X‐ray absorption fine structure analysis elucidates its mechanism, which is that Eu 2+ and Mn 2+ are constrained to form Eu 2+ –Mn 2+ pairs with a small distance 3.7 Å caused by the local environment relaxation inducement. Meanwhile, by creating an unhindered energy flow between Eu 2+, Mn 2+ and K + /O 2− defect levels through ET and multilevel electron trapped and recombination process, the KAO:Eu 2+, Mn 2+ phosphors perform superb photoluminescence property with a high color purity of 83%, an excellent thermal stability (94%@200°C), and unexceptionable internal and external quantum efficiencies of 91.7% and 66.4%, which all are superior to characteristics of commercial β‐SiAlON:Eu 2+ phosphor. Moreover, the white LED fabricated using KAO:Eu 2+, Mn 2+ to provide green component shows a wide color gamut of 105% National Television System Committee. These results indicate a potential for an application of our material in LCD–LED backlights, and the design of such local relaxation‐induced structure provides a significative reference to develop the new narrow‐band emitters. Abstract : A nearly single‐peak narrow‐band green emission phosphor KAO:Eu 2+, Mn 2+ with excellent photoluminescence properties is developed by structure constraint effect.